Levels and characteristics of the digital divide: a case study of Lithuania - Šuminas, Andrius; Gudinavičius, Arūnas; Aleksandravičius, Arnas (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] After the sudden growth of popularity of IT and the internet, scholars have noticed emerging differences between usage or non-usage of the internet among different individuals and groups of society. These differences were defined as the digital divide. At first, more attention was given to the differences of access to IT and the internet, but today, scholars are focusing on another level of the digital divide – one determined by skills, perceived value and motivation. In this article, we examine the characteristics of the different levels of the digital divide by analyzing various statistical indicators. We seek to explain which groups of Lithuanian society feel the social and digital divide the most; also, we explain the features and changes of every level of the digital divide.